Aktivitas Antibakteri Ekstrak Terpurifikasi Parsial Mangrove (Rhizophora mucronata Lamk) - Herlina Rante, Rosany Tayeb, Sri Hidayanti N (STIFA Makassar, 2016)
The purpose of this study are to determine the antibacterial activity of mangrove (Rhizophora mucronata Lamk) and determine the lowest concentration of mangrove leaf extract can inhibit the growth of bacteria. Mangrove leaves macerated with methanol and then partitioned with solid liquid extraction method successively with n-hexane, chloroform, and ethylacetate. Thus obtained extract methanol, n-hexane, chloroform, ethyl acetate and ethyl acetate extracts insoluble. Each extract was tested antibacterial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923 with agar diffusion method. The methanol extract, can inhibit the growth of E. coli at concentrations up to 200 mg/mL of 10.7 mm. Chloroform extract and extract of 8.1 mm by 8.2 mm ethylacetate to a concentration of 25 mg/mL, while the bacterium S. aureus, methanol extract and insoluble ethyl acetate extract is able to inhibit S. aureus up to a concentration of 50 mg/mL with a diameter of inhibition respectively 8.2 mm and 7.2 mm. At the chloroform extract can inhibit the growth of bacteria to a concentration of 6.25 mg/mL of 9.8 mm and 9.2 mm ethyl acetate extract to a concentration of 12.5 mg/mL. Chloroform and ethyl acetate extracts of the active compound thought to contain alkaloids, flavonoids, terpenoids, and tannin